FAKTOR DETERMINAN YANG BERHUBUNGAN DENGAN PARTISIPASI PEMERIKSAAN IVA PADA WANITA USIA SUBUR - Muhammad, Yudhianto; Arief, Rania Marwa Dinar; Tarigan, Gita Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Cervical cancer is an important health problem for women throughout the world because it is the highest cause of death both nationally and globally. This study aims to assess various determinant factors that influence the participation of Women of Childbearing Age (WUS) to carry out IVA test in the Puskesmas Pesanggrahan working area. This research is an analytical observational study with a cross sectional design. Primary data was collected through questionnaires from respondents, while data on IVA test that carried out by WUS was taken from the Puskesmas Pesanggrahan in the period March – April 2024. The population of this study was all WUS who lived in the Petukangan Selatan Subdistrict, Pesanggrahan District, who met the research criteria. A total of 109 WUS became respondents in this study. In this study, the p value < 0.05 which showed a significant correlation was found in the determinant factors of knowledge related to IVA test, access to information related to IVA test, husband's support, support from health workers, support from health cadres, and support from friends. Determinant factors that are found to be related can be a focus for community health centers to develop promotive efforts on targets that determine decisions to WUS in carrying out IVA test, apart from the knowledge regarding IVA test among WUS can continue to be improved through health promotion programs at community health centre.